MENINGKATKAN KOSAKATA DENGAN MEDIA WORDWALL PADA ANAK KELOMPOK KELAS B DI TK ADINDA SURABAYA - CATUR YAWALIUL FATIMAH; Sugito Muzaqi (MOTORIC, 2026)
Language is one of the learning programs in Kindergarten aimed at developing fundamental skills that enable students to communicate orally with their environment. In language instruction, one aspect that preschool children learn is word mastery, which aims to increase the number of words students can comprehend. Based on interviews with teachers, the letter mastery of students in Class B at Adinda Kindergarten, Sidosermo, Wonocolo Subdistrict, Surabaya City, is still low. The primary issue significantly affecting students' word mastery is the use of inappropriate teaching methods by teachers and the limited utilization of instructional media. Therefore, appropriate teaching methods and media are required to enhance word mastery. One media that can facilitate more enjoyable classroom learning is the digital game application called Wordwall. The research was conducted in Class B at Adinda Kindergarten, with a total of 9 students observed. The assessment criteria were categorized as follows: poor (1-4), fair (5-8), good (9-12), and excellent (13-16). The observation was divided into three stages: pre-cycle, cycle I, and cycle II. In the pre-cycle stage, the average score of the 9 students was 7, categorized as good. In cycle I, the average score increased to 10, also categorized as good. Finally, in cycle II, the average score further improved to 11.89, remaining in the good category. Keywords: drawing creativity, plant media, class action